Anti-fungal T cell responses in the lung and modulation by the gut-lung axis. (August 2020) - Scheffold, Alexander; Bacher, Petra
Highlights: Ubiquitous airborne fungi differentially induce protective immunity or tolerance. Chronic exposure to A. fumigatus induces primarily Treg-mediated tolerance. The majority of A. fumigatus -associated diseases resemble immune pathologies. Microbiota exert antigen-specific and non-specific (innate) immune modulation. Abstract : The lung is a central organ for immune-environmental interactions ranging from tolerance against harmless substances to protection against pathogens, which are particularly sensitive to regulation by the intestinal microbiota. Airborne fungi, can cause variety of diseases, including allergies and inflammatory disorders, as well as life-threatening invasive infections. Remarkable differences exist between ubiquitous fungal species with regard to protective immune mechanisms. Recent data have surprisingly identified Aspergillus-specific regulatory T cells as an essential tolerance checkpoint and provided mechanistic insight for the loss of tolerance in the course of immune pathologies. Furthermore, pathogenic Th17 cells in Aspergillus-associated inflammatory disease seem to be induced by cross-reactivity to the intestinal commensal Candida albicans . Here we review and discuss what is known about fungus-specific T cell responses in the lung how they are modulated by the gut-lung axis and in particular discussing the modulation of adaptive immune responses by cross-reactivity to the microbiota.